Molecular structures and biological evaluation of 2-chloro-3-(n-alkylamino)-1,4-napthoquinone derivatives as potent antifungal agents - Pawar, Omkar; Patekar, Ashwini; Khan, Ayesha A.; Kathawate, Laxmi; Haram, Santosh K.; Markad, Ganesh; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Derivatives of 2-chloro-3-(n-alkylamino)-1,4-naphthoquinone (1-alkyl: methyl; L-1, ethyl; L-2, propyl; L-3 and butyl; L-4) have been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible spectroscopy, LC-MS and single crystal X-ray diffraction studies. Antifungal activity of L-1 to L-4 has been evaluated against Candida tropicalis, Candida albicans and Cladosporium herbarum. The intramolecular hydrogen bonding affects the N-H vibrational frequency in L-2 (3273 cm(-1)). The single crystal X-ray structure reveal that L-1 and L-3 crystallizes in triclinic P-1, whereas L-2 crystallizes in orthorhombic Pca2(1), space group. An extensive intra and intermolecular hydrogen bonding interactions were observed in L-1 to L-3 which leads to molecular association. Intramolecular N-H center dot center dot center dot O hydrogen bonding were observed in L-1 to L-3. Moreover pi-pi stacking interactions were observed between the quinonoid rings of L-1 and L-3, however no such interactions were observed in L-2. An electrochemical study showed molecular association of L-1 to L-4 in DMSO solution. Compounds L-1 to L-4 were found to be potent antifungal agents against all the three strains, especially against C. tropicalis. Amongst these promising antifungal candidates, L-1 showed better activity compared to the clinically administered antifungal drug Amphotericin B and Nitrofurantoin with MIC = 1.25 mu g ml(-1) and MIC = 0.025 mu g ml(-1) respectively against C. albicans. Structure and activity relationship (SAR) study suggest a LogP value of similar to 2.0 and the cyclic voltammetry studies reveals additional chemical processes for L-1, which exhibits maximum activity against all fungal strains. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Antifungal activity; LogP; Naphthosemiquinone; pi-pi stacking

First naphthosemiquinone complex of K+ with vitamin K3 analog: experiment and density functional theory - Kathawate, Laxmi; Gejji, Shridhar P.; Yeole, Sachin D.; Verma, Prakash L.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2015)
Synthesis and characterization of potassium complex of 2-hydroxy-3-methyl-1,4-naphthoquinone (phthiocol), the vitamin K3 analog, has been carried out using FT-IR, UV-Vis, H-1 and C-13 NMR, EPR, cyclic voltammetry and single crystal X-ray diffraction experiments combined with the density functional theory. It has been observed that naphthosemiquinone binds to two K+ ions extending the polymeric chain through bridging oxygens O(2) and O(3). The crystal network possesses hydrogen bonding interactions from coordinated water molecules showing water channels along the c-axis. C-13 NMR spectra revealed that the complexation of phthiocol with potassium ion engenders deshielding of C(2) signals, which appear at delta = similar to 14.6 ppm whereas those of C(3) exhibit up-field signals near delta similar to 6.9 ppm. These inferences are supported by the M06-2x based density functional theory. Electrochemical experiments further suggest that reduction of naphthosemiquinone results in only a cathodic peak from catechol. A triplet state arising from interactions between neighboring phthiocol anion lead to a half field signal at g = 4.1 in the polycrystalline X-band EPR spectra at 133 K. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: C-13 NMR; DFT; hydrogen bonding; Naphthosemiquinone; Phthiocol; Vitamin K3